Al-Shabakāt al-ijtimā‘īyah wa al-fikrīyah bayn muslimī Lombok wa Sumatera: Dirāsah fī tuḥfah wa makhṭūṭ Sasak - Jamaluddin, Jamaluddin (Studia Islamika, 2019)
This article discusses the socio-intellectual networking of Indonesian Muslim communities, especially in Sumatra and Lombok communities. The relationship between them is observed through ancient manuscripts and artifacts, while the philological and archeological approach are utilized to reconstruct its history. From these two primary sources, this article finds that the Sumatra-Lombok relationship had long existed and both of them had been influencing one another. One of the pieces of evidence held by the Sasak People in West Nusa Tenggara proves this influence existence. It is also supported by the existence of Malay-language manuscripts which are currently kept by the Sasak people. Supporting the written evidence, archaeological evidence also espouses the article’s argument wherein it can be found from the presence of Aceh's gravestones found in Raja Selaparang's burial complex in Lombok, West Nusa Tenggara. On the basis of these two historical sources, the article proves that the connectedness of the Sumatran-Lombok community had existed before the era of the Islamic kingdom in the Nusantara. When the emergence of the Islamic empire, the relationship between the two was even further strengthened by the presence of the scholars from both regions who came and settled in Mecca.